Customer Satisfaction Based on User Perceptions in a Delivery Company in Peru - Del Castillo, Miguel Daniel Ramirez; Chavez-Romero, Zaida Brenida; Alvarado-Silva, Carlos Alexis; De Oliveira, Geraldo Cesar Rosario [UNESP]; Gaytan-Reyna, Sassy Emperatriz (Richtmann Publishing, 2023)
The aim of this research is to identify the factors impacting customer satisfaction, focusing on customer perceptions within one of the country's most prominent delivery companies, specifically centered in the city of Chiclayo, Peru. The study utilizes the SERVPERF model, which gauges customer perceptions across five dimensions: reliability, responsiveness, security, empathy, and tangibility. Interviews were conducted with the manager and several delivery drivers in the city to comprehend operational processes. To gather unbiased customer opinions, a survey was administered to 196 customers. The results indicate that customers assess the company's service quality as average. Despite the elevated demand, customers display a relatively low level of contentment with the service provided. Furthermore, the research explores the extent of customer satisfaction. Through Pearson's correlation analysis, it was ascertained that the dimensions exerting influence on satisfaction encompass reliability, security, and empathy. The study also establishes that the degree of satisfaction averages out and is intrinsically tied to the quality of service.
Keywords: customer satisfaction; delivery service; service quality; SERVPERF